Emerging paradigms in metastasis research - Abdul Pari, Ashik Ahmed; Singhal, Mahak; Augustin, Hellmut (Journal of experimental medicine, 2021)
Historically, therapy of metastatic disease has essentially been limited to using strategies that were identified and established to shrink primary tumors. The limited efficacy of such treatments on overall patient survival stems from diverging intrinsic and extrinsic characteristics of a primary tumor and metastases originating therefrom. To develop better therapeutic strategies to treat metastatic disease, there is an urgent need to shift the paradigm in preclinical metastasis research by conceptualizing metastatic dissemination, colonization, and growth as spatiotemporally dynamic processes and identifying rate-limiting vulnerabilities of the metastatic cascade. Clinically, while metastatic colonization remains the most attractive therapeutic avenue, comprehensive understanding of earlier steps may unravel novel metastasis-restricting therapies for presurgical neoadjuvant application. Moving beyond a primary tumor-centric view, this review adopts a holistic approach to understanding the spatial and temporal progression of metastasis. After reviewing recent developments in metastasis research, we highlight some of the grand challenges and propose a framework to expedite mechanism-based discovery research feeding the translational pipeline.
December 18 2020
Gesehen am 06.05.2021